Surgical Treatment of Persistent Fetal Vasculature and Visual Rehabilitation: One-Year Followup - N. Kozeis; K. T. Tsaousis; D. Gidaris (Case Reports in Medicine)
We present the management and postoperative course of a persistent fetal vasculature (PFV) case. A four-year-old girl visited the Eye Department of Hippokration, General Hospital of Thessaloniki due to reduced visual acuity of her left eye. She was diagnosed with PFV and underwent surgery (lensectomy, capsulorhexis of the posterior capsule, insertion of an intraocular lens in the posterior chamber, and posterior vitrectomy) in order to dissect the PFV. Along with the postoperative medical care, she underwent intensive treatment for amblyopia. The postoperative course was uncomplicated, and the visual acuity of her left eye improved from hand movement to 20/25 with proper correction. Patients with unilateral PFV and gradually deteriorating visual acuity could be good candidates for a combined surgical procedure, as the one described above, with a good prognosis.